2018
DOI: 10.18805/lr-3850
|View full text |Cite
|
Sign up to set email alerts
|

Study on the effect of different levels of organic and inorganic fertilizers on microbial enzymes and soil mesofauna in soybean ecosystem

Abstract: Soybean (Glycine max (L) Merril). is also called Golden bean belongs to family Fabaceae is native to China having high nutritive value and oil content. Due to usage of inorganic fertilizers the fertility of soil and yield soybean has declined. Organic manures known to increase the soil fertility, structure and also influence the microbial enzymes activity and soil mesofauna. In this context the present investigation was undertaken to study, the different doses of farm yard manure and chemical fertilizers on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
5
0
1
Order By: Relevance
“…Treatment combinations or control resulted in no differences in active nodule number. Prasanti et al [10] reported that Organic manures had been shown to improve soil fertility and structure and affect microbial enzyme activity and soil biodiversity. The investigation at GKVK, Bangalore, during 2013-2014 revealed that 20 tons of FYMha -1 showed a higher abundance of soil mesofauna (18.53) when compared to inorganic fertilizer and the recommended treatment, showing an abundance of soil mesofauna of only 10.30 and 12.35, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment combinations or control resulted in no differences in active nodule number. Prasanti et al [10] reported that Organic manures had been shown to improve soil fertility and structure and affect microbial enzyme activity and soil biodiversity. The investigation at GKVK, Bangalore, during 2013-2014 revealed that 20 tons of FYMha -1 showed a higher abundance of soil mesofauna (18.53) when compared to inorganic fertilizer and the recommended treatment, showing an abundance of soil mesofauna of only 10.30 and 12.35, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…It was a two-factor Randomized Complete Block Design experiment consisting of three replications. The first factor was the application of cow manure at four rates (10,15,20, and 25 t ha 1 ), and the second factor was nitrogen source, including urea at a dose of 100 and 150 t ha -1 and ammonium sulfate (AS) at a dose of 200 and 300 kg ha -1 . Control treatment was jack bean monoculture, applied with manure and nitrogen fertilizer at minimum rates.…”
Section: B Experimental Designmentioning
confidence: 99%
“…Также численность и разнообразие представителей мезофауны сокращало применение минеральных удобрений, что согласуются с результатами G. Prasanthi с соавт. (39).…”
Section: рис 2 численность основных групп мезофауны в почве в зависимости от способа ее обработкиunclassified
“…In the field of biotechnology, the process of producing enzymes from microorganisms is one of the most current approaches with a bright future (Prasanthi et al, 2019;Sharma et al, 2021). Pectinase is an acidic polysaccharide with a basic structure that includes D-galacturonic acid molecules in the main chain connected by a (1-4) bond and Arabinose and Xylose molecules in the side chain (Mohnen, 2008).…”
Section: Introductionmentioning
confidence: 99%